Caledon Hockley As An Antagonist In James Cameron’s Titanic (1997) Movie Script - Liora Samantha Valent Santoso; Putut Handoko; Hariyono (PT. Padang Tekno Corp, 2026)
This study aims to analyze the portrayal of Caledon Hockley as an antagonist in James Cameron’s Titanic (1997) movie script, focusing on his antagonist functions and characterization. The analysis draws on the theories of Holman, Abrams, Smiley, and Forster to examine Caledon’s antagonist functions, characterization, and contribution to the screenplay’s moral and thematic construction. This study employs a descriptive qualitative method. The finding shows that data are to reveal that Caledon, characterized by traits such as possessiveness and class superiority, fulfills essential antagonist functions by opposing the protagonists and generating conflicts. His consistent traits classify him as a flat character, and his role extends to exposing moral values and reinforcing themes of freedom, love, social inequality and power. Ultimately, Caledon serves both as a source of conflict and as a rhetorical device that enhances the screenplay's narrative and thematic depth, underscoring the importance of antagonist characterization in literary analysis.